Subliminal how you unconscious mind rules your behavior - "Mlodinow,Leonard" (New york, 2012)
Over the past two decades of neurological research, it has become increasingly clear that the way we experience the world--our perception, behavior, memory, and social judgment--is largely driven by the mind's subliminal processes and not by the conscious ones, as we have long believed. In Subliminal, Leonard Mlodinow employs his signature concise, accessible explanations of the most obscure scientific subjects to unravel the complexities of the subliminal mind. In the process he shows the many ways it influences how we misperceive our relationships with family, friends, and business associates; how we misunderstand the reasons for our investment decisions; and how we misremember important events--along the way, changing our view of ourselves and the world around us.
Keywords: Subliminal